2019
DOI: 10.25271/sjuoz.2019.7.4.629
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Urinary Tract Infections and Their Antimicrobial Sensitivity Among Diabetic and Non Diabetic Patients in Zakho

Abstract: Background: Urinary tract infection (UTI) is one of the most common bacterial infections in diabetics and non-diabetics. Worldwide about one hundred fifty million people are infected with UTI each year. Indifference in diabetes management has been shown to increase the risk of complications. This may lead to different microbial infections including UTI. UTI is often treated with various broad-spectrum antibiotics due to concerns about infection with resistant organisms. Objective: The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
2
6
1
Order By: Relevance
“…Diabetic patients suffer commonly from fungal UTI who rather than bacterial especially among those are hospitalized for a long period, (Joshi, N. et al, 1999) catheterized, and frequently using the parenteral antibiotic . This result (Jameel was in contrast to other studies that found a higher risk of UTI among DM patients A.Y. et al, 2019A.Y.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Diabetic patients suffer commonly from fungal UTI who rather than bacterial especially among those are hospitalized for a long period, (Joshi, N. et al, 1999) catheterized, and frequently using the parenteral antibiotic . This result (Jameel was in contrast to other studies that found a higher risk of UTI among DM patients A.Y. et al, 2019A.Y.…”
Section: Discussioncontrasting
confidence: 99%
“…et al, 2016). The same results were obtained from previous studies conducted in different places in the world [ (Jameel A.Y. et al, 2019;Bonadio, M. et al, 2006& Tan, C.W.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Such as in Zakho city, a rate of 43.20% isolates of E. coli was detected among UTIs patients. [22] While in Duhok city, a much higher rate of UPEC infection which was 74.4% (276/371) was reported in women. [20] Furthermore, in Erbil and Sulaimania cities, high prevalence (42% vs 30%, respectively) of the UPEC were isolated from pure and mixed cultures were.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of P. mirabilis toward the antibiotics used in this study was somewhat similar to other studies performed in Kurdistan Region /Iraq and other developing countries. For example, in Zakho city Jameel and Artoshi (2019) showed that these bacteria displayed low sensitivity rates to Chloramphenicol 14.29% and Amikacin 28.57%. Naqid et al (2020) in Duhok city demonstrated that P. mirabilis displays high resistance to Ampicillin 77.8%, but low resistance to Gentamicin 11.1%.…”
Section: Antibiotics Sensitivity Testmentioning
confidence: 99%